A proposed form for the Combined Assurance report and its impact In achieving sustainable development in the Iraqi economic units (Journal of Accounting and Financial Studies ( JAFS ), 2022)
Despite the importance of sustainable development and its dimensions in developing performance and supporting competitive advantage in economic units, there is a gap and lack of coordination between Combined Assurance  providers (management, internal audit, external audit) to report on sustainable development, and the research aims to propose a model for the Combined Assurance report to achieve development sustainable development in the Iraqi economic units, especially the Baghdad Municipality, enables assurance providers to coordinate efforts that lead to the achievement of Combined Assurance, The research found the proposed model for the Combined Assurance report in achieving sustainable development in the Iraqi economic units, especially the Baghdad Municipality, which leads to improving the assurance processes among the assurance providers about economic, environmental and social risks and getting rid of duplication that hinders the achievement of goals and finding practical ways to preserve resources and improvement to achieve sustainable development, The research presented a number of recommendations, represented by the need to implement the joint assurance in the Iraqi economic units, especially the Baghdad Municipality, because it gives a comprehensive view to the senior management of the potential risks related to economic, environmental and social activities, as well as the need to adopt the proposed model for the Combined Assurance report in achieving sustainable development in economic units. Iraqi.